Dually Labeled Neurotensin NTS1R Ligands for Probing Radiochemical and Fluorescence-Based Binding Assays - Ertl, Fabian J.; Kopanchuk, Sergei; Dijon, Nicola C.; Veikšina, Santa; Tahk, Maris Johanna; Laasfeld, Tõnis; Schettler, Franziska; Gattor, Albert O.; Hübner, Harald; Archipowa, Nataliya; Köckenberger, Johannes; Heinrich, Markus; et al. (Journal of Medicinal Chemistry, 2024)
The determination of ligand-receptor binding affinities plays a key role in the development process of pharmaceuticals. While the classical radiochemical binding assay uses radioligands, fluorescence-based binding assays require fluorescent probes. Usually, radio- and fluorescence-labeled ligands are dissimilar in terms of structure and bioactivity, and can be used in either radiochemical or fluorescence-based assays. Aiming for a close comparison of both assay types, we synthesized tritiated fluorescent neurotensin receptor ligands ([3H]13, [3H]18) and their nontritiated analogues (13, 18). The labeled probes were studied in radiochemical and fluorescence-based (high-content imaging, flow cytometry, fluorescence anisotropy) binding assays. Equilibrium saturation binding yielded well-comparable ligand-receptor affinities, indicating that all these setups can be used for the screening of new drugs. In contrast, discrepancies were found in the kinetic behavior of the probes, which can be attributed to technical differences of the methods and require further studies with respect to the elucidation of the underlying mechanisms.
CRIS-Team Scopus Importer:2024-09-20